"Tears of joy" & "smiles of joy" prompt distinct patterns of interpersonal emotion regulation. Issue 5 (4th July 2018) - Aragón, Oriana R.; Clark, Margaret S.
ABSTRACT: Close relationship partners often respond to happiness expressed through smiles with capitalization, i.e. they join in attempting to up-regulate and prolong the individual's positive emotion, and they often respond to crying with interpersonal down-regulation of negative emotions, attempting to dampen the negative emotions. We investigated how people responded when happiness was expressed through tears, an expression termed dimorphous. We hypothesised that the physical expression of crying would prompt interpersonal down-regulation of emotion when the onlooker perceived that the expresser was experiencing negative or positive emotions. When participants were asked how they would behave when faced with smiles of joy, we expected capitalization responses, and when faced with tears of joy, we expected down-regulation responses. In six experimental studies using video and photographic stimuli, we found support for our hypotheses. Throughout our investigations we test and discuss boundaries of and possible mechanisms for such responsiveness.